Pore water geochemical data for sediment cores obtained during ALKOR cruise AL543 - Florian Scholz (PANGAEA, 2022)
During RV Alkor cruise AL543 (23.08.2020 – 28.08.2020), CTDs were deployed and multiple corers (MUC) were retrieved at 11 stations in Kiel Bight in the western Baltic Sea. Water column samples were collected for the analyses of nutrient (nitrate, nitrite, phosphate and silica) concentrations using an autoanalyzer and oxygen concentrations by Winkler titration. The pore water was extracted from the MUCs and analyzed onboard for ammonia, phosphate, silica and dissolved ferrous iron (photometry), chloride and sulfate (ion chromatography) as well as total alkalinity (titration). The data and samples collected during AL543 will be used to investigate (i) the impact of coastal erosion on sedimentary processes and (ii) how the interplay of benthic and pelagic processes determine the distribution of trace elements and their isotopes in the water column.
In: Scholz, F (2023): Water column and pore water data obtained during RV Alkor cruise AL543 [dataset publication series]. PANGAEA, https://doi.org/10.1594/PANGAEA.954246